Reconciliation between preschool work, family and profesional life (Praxis Educativa, 2025)
This research is qualitative and has a biographical-narrative approach whose objective is to present the life experiences of a preschool teacher facing the return to face-to-face work activities. In-depth interviews, autobiographical texts and the life history technique were used in data collection. The results showed the conciliation between school and domestic activities that includes taking care of daughters and household chores, highlighting family support networks and the use of conciliatory strategies, while, on the professional side, the decision to pause doctoral studies temporarily. It is concluded that the conciliation of activities in the different roles played had a positive effect in facing the return to face-to-face work, which makes it necessary for educational authorities to focus their efforts on developing strategies and policies that guarantee conciliation in the roles for the well-being of female teachers.
Keywords: school work; family life; professional life; entailment; female teacher